Utilization of Internet of Things (IoT) in Water Quality Monitoring for Sustainable Fish Farming: A Systematic Literarture Review - MUTIARA ALAMSYAH, KHARISMA WIDYA; LEONI CAHYA ELRINOLLA; CHARMELIA YUNIZAR JERANDU; SUYOTO (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2025)
This study presents a systematic review on the integration of Internet of Things (IoT) technology in water quality monitoring. The objective of this research is to understand how IoT enhances the accuracy and capability of real-time water quality monitoring, as well as to summarize empirical evidence regarding its effectiveness in reducing the risks and impacts of water pollutants. Our primary contribution is the presentation of a general model of IoT-based water quality monitoring systems that captures monitoring and data analysis activities, along with an examination of the main barriers to its implementation in the aquaculture sector, including technical, operational, and economic challenges. We also summarize potential solutions to address these barriers, such as increased investment in IoT infrastructure, workforce training, and the development of policies that support IoT adoption. The study finds that IoT integration significantly enhances the accuracy and efficiency of water quality monitoring, enabling early detection of pollutants and faster decision-making. However, challenges such as high costs, limited infrastructure, and the need for specialized technical expertise remain significant obstacles. Overall, existing literature reports largely positive effects of IoT adoption in water quality monitoring, though there remains room for further exploration in overcoming these barriers and enhancing the adoption of this technology in the aquaculture sector.